2022
DOI: 10.3389/fphar.2022.1012433
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological interventions on smoking cessation: A systematic review and network meta-analysis

Abstract: Objective: A network meta-analysis based on randomized controlled trials was conducted to investigate the effects of pharmacological interventions on smoking cessation.Methods: English databases were searched to obtain randomized controlled trials reporting the effect of pharmacological interventions on smoking cessation. The risk of bias for the included trials was assessed using Cochrane Handbook tool. Stata 15.1 software was used to perform network meta-analysis, and GRADE approach was used to assess the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…However, Siskind et al showed that varenicline + NRT ranked first in achieving sustained abstinence 32 . Shang et al found that a combination of mecamylamine and nicotine was the best intervention 33 . This difference may have resulted from an emphasis on RCTs reporting on antidepressant treatment in our study, whereas Shang et al's network meta‐analysis evaluated the therapeutic effect of all drug interventions for tobacco, leading to more heterogeneity.…”
Section: Discussionmentioning
confidence: 77%
“…However, Siskind et al showed that varenicline + NRT ranked first in achieving sustained abstinence 32 . Shang et al found that a combination of mecamylamine and nicotine was the best intervention 33 . This difference may have resulted from an emphasis on RCTs reporting on antidepressant treatment in our study, whereas Shang et al's network meta‐analysis evaluated the therapeutic effect of all drug interventions for tobacco, leading to more heterogeneity.…”
Section: Discussionmentioning
confidence: 77%
“…36 Nicotine replacement therapies in the form of gum, lozenges, and patches, also have established efficacy, particularly when combined with other medications for tobacco treatment. 14,35,37,38 In this community served by safety-net clinics, access to NRT at no cost is critical to ensure that prescriptions are filled and pharmacotherapies are used. Likewise, no cost access to varenicline, which only recently went off patent, is highly beneficial to individuals served by these clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, utilization of TUD pharmacotherapies has been shown to improve the success rates of smoking cessation, relative to cessation efforts without pharmacotherapy. 10,38 According to the Exploration, Preparation, Implementation, Sustainment Again would be helpful to have the abbreviation here: (EPIS) framework, sustainment is essential for continued meaningful change and public health impact. 26 Results from this project provide initial evidence of sustainment through clinician-level adoption of these evidence-based treatments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations